Short‐term impact of beaver dam analogues on streambank erosion and deposition in Semi‐Arid landscapes of the Western USA. (2nd June 2021) - Pearce, Casey; Vidon, Philippe; Lautz, Laura; Kelleher, Christa; Davis, Julianne
Abstract: River systems in the mountain western USA have been shaped by the presence of beavers for millennia. However, beavers have been extirpated from the landscape in many places, leading to excessive stream incision and streambank erosion. One common strategy to mitigate this issue is to deploy beaver dam analogue (BDAs) as a stream restoration technique. Although BDAs are intended to reduce erosion and stream incision, few studies directly document the impact of BDAs on stream channel geomorphology. This study, therefore, assesses how a complex of five BDAs along a 150 m long stream reach in Red Canyon Ranch near Lander, WY impacts stream bank erosion and deposition and channel evolution over a 1‐year period post‐installation. Relative to control locations not impacted by BDAs, the BDA reach showed greater spatial heterogeneity in erosion and deposition patterns than control locations, as well as less overall erosion. However, each BDA had unique effects on channel morphology. Large amounts of deposition were found at the most upstream BDA remaining after the first year at both inner and outer meander locations. High flow events created breaches that likely produced significant stream bank erosion observed immediately downstream of the BDA complex. From a design standpoint, the only BDAs that remained after a year were those built around fence posts inserted into the stream bed with a percussion fence post driver. Overall, our short‐term data indicate that BDAs can be successfully used as a stream restoration practice to reduce stream bank erosion and increase channel geomorphological heterogeneity.